Diversidade organizacional e envelhecimento humano: um estudo com profissionais de 40 ou mais anos de idade - Neves, Juçara Pereira da Costa (2017)
This research addresses issues related to prejudice and discrimination of people aged 40 or over in the work context and the challenges faced by these individuals at the time and a possible professional relocation at that stage of human life. For this, a bibliographical research was conducted on issues related to human aging, global longevity and longevity in Brazil, organizational diversity, people management, work, labor market, individual, social psychology and ethics. A quantitative-descriptive research was also performed with data obtained through an online questionnaire, answered by 56 professionals aged 40 years or over. First, the statistical analysis was based on the presentation and description of the frequency diagrams corresponding to the data collected for the various questions formulated. As a complementary study, the chi-square test of independence was applied in order to verify the existence or not of association between certain variables. The data revealed that professionals aged 40 and over perceived the existence of prejudice and age discrimination in the work context, as well as several challenges faced during the professional relocation process after 40 years of age. This research aims to contribute to discussions and new studies focused on this topic. In addition, this study aims to assist professionals in the area of social Psychology, human resources and/or people management, promoting information and reflection on the subject, in order to work for social inclusion in companies of people with that age group